Brand Equity As An Interveing Variable In The Relationship Between Celebrity Endorser And The Firm’s Performance Of Medan City Cakes - Riza Fanny Meutia; Siregar, Findi Ruzika Audini (Journal Of Management Analytical and Solution (JoMAS), 2022)
This research aims to analyze the celebrity endorser on the performance of the Medan City cakes through brand equity as an intervening variable. The target population of the researcher is all people of Medan City who have bought one or more Medan City cakes, such as: Medan Napoleon, Medan Par Par, Bolu Toba Medan and Medan Mulaka at outlets/stores so the number can never be known. The research sample used 300 people, namely the people of Medan City who had bought one or more Medan City cakes, such as: Medan Napoleon, Medan Par Par, Bolu Toba Medan and Medan Mulaka at outlets/stores through the simple random sample method. The hypothesis tested in this study used the t value test. From the results of the tests that have been carried out, it can be obtained that the celebrity endorser variable on the firm performance variable through the brand equity as an intervening variable is a positive and significant relationship. Celebrity endorsers should reflect the company's value and it is hoped that celebrity endorsers will continue to improve their performance so that it creates trust and strong attraction by target consumers and can increase the brand equity of Medan City cakes.